Developing Cultural Competence In Paramedic Education: An Analysis of Culturally Diverse Training Equipment Amongst Universities In Australia And New Zealand - Ricky Lam; Rhys Hillsley; Jun Steele; Steve Whitfield (Bond University, 2022)
_Aim_: This study aims to identify the availability of culturally diverse training equipment across approved paramedicine undergraduate degrees in Australia and New Zealand and explore its impact on a university's ability to teach paramedic care that is culturally safe and competent. _Methodology_: Academic staff from 16 university accredited paramedicine programs across Australia and New Zealand were invited to complete an online survey about their access to culturally diverse training equipment and their ability to teach culturally competent paramedic care. Responses were then summarised in tables. _Results_: There were a total of 14 responses. The total number of students enrolled in each program ranged from <100 - >500. There are a total of at least 140 ALS manikin, only twelve (n=12) identified as reflecting people of colour. In addition to this, there were 145 cannulation arms, 27 (n=27) were identified as being of colour. Most respondents believed that their university developed emerging skills in culturally competent paramedic care. _Conclusion_: Access to culturally diverse training equipment across Australian and New Zealand universities is limited. Access to culturally diverse training equipment impacts a university's ability to teach paramedicine students culturally safe practice through simulation-based learning. Greater access to culturally diverse equipment plays an important role in a university's ability to make students more culturally aware. It was concluded that acquiring more culturally diverse training equipment will lead to greater levels of cultural competence amongst paramedicine students.